Louisiana Romani: Constructing Race in the Colonial Caribbean - Ostendorf, Ann (Romano džaniben, 2021)
Romani experiences in the eighteenth-century French (and then Spanish) colonyof Louisiana reveal how diverse evolving American racial regimes were informedby and overlapped with older European anti-Romani sentiments. Many Romaappear in Louisiana records at the crux of solidifying racial categories. Romaniwomen who married and partnered with Black and Native American men weremost consistently labeled with words that referenced their Romani heritage. Theirsexual choices reveal a perception of their racial liminality that only graduallydisappeared. A self-described "Boheme" man's court testimony, the only knownself-narration by a colonial Caribbean Rom, attests to his struggle to situate himselfinto the distinctively fluid racialized social order of Louisiana. Such choices revealRomani attempts to engage racial categories to suit their own interests. Yet withoutguaranteed full membership into colonial whiteness, their subjugated positionlimited their possibilities. A journey across the Atlantic forced French Roma toconfront, and then position themselves into, a new social order not yet detachedfrom the one they left behind.
Keywords: Bohemian; Gitana; Roma; Louisiana; New Orleans; race; empire; marriage